Leisure Time Physical Activity of Students of The Institute of Health Sciences at The State Higher Vocational School in Tarnów - Eligiusz Madejski; Marta Bibro; Katarzyna Wódka; Małgorzata Łaczek-Wójtowicz; Roger Madejski; Jacek Szalewski (University of Applied Sciences in Tarnow, Poland, 2018)
Introduction: Physical activity, apart from enhancing proper body functioning, is a natural need of every human being, and taken up regularly brings numerous health benefits. The aim of the research was to define the level of physical activity in leisure time as well as to present the forms of physical activity preferred by students. Material and methods: The research was conducted in the academic year 2017/2018 among the first year students of The State Higher Vocational School in Tarnów, majoring in Physical Education, Physiotherapy and Nursing. The survey covered the total of 209 students, 153 females (73.2%) and 56 males (26.8%). A diagnostic survey was applied as the research method, and the empirical material was collected with the use of a questionnaire. Results: The research showed that the level of students' physical activity varied depending on both sex and the field of study. The majority of the respondents (66.5%) showed a low level of physical activity. The female students most frequently practised swimming (22.2%) and running (13.1%), whereas the male students preferred football (32.1%), gym workout (17.9%) and, similarly to the females, swimming (14.3%). Conclusions: On the basis of the research results and the formulated conclusions it can be stated that taking decisive and effective actions in order to develop positive attitudes towards physical culture among children and youth and to prepare them for lifelong care for their body should be a priority.